Preliminary lessons learned from facilitating group work for justice-involved women in rural communities: A case study in an Alabama correctional facility in the era of COVID-19. (September 2020) - Beech, Haley H; Sutton, Amber; Potok, Carol
This essay offers a glimpse into implementing and facilitating a 6-week psychoeducational health group inside a women's correctional facility. Using a case study example, this essay discusses conceptualization, interagency collaboration, and lessons learned in the field. Within group work, social workers have a unique opportunity to create safer spaces, recognize trauma histories, and address issues disproportionately affecting justice-involved women. Many lessons learned can be applied across settings, domestically and abroad. With preparation and facilitation, groups can be transformational spaces where women can find camaraderie with one another even in the midst of a pandemic.